Students’ Perceptions of The Use Of Total Physical Response (TPR) Method in Teaching Vocabulary in British English School Makassar - Tunru, Bunga; Pammu, Abidin; Nasmilah, Nasmilah (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
The Total Physical Response (TPR) method is a teaching strategy that helps children learn the names of body parts through movement and rhythm.The purpose of this study is to find out the students’ perceptions of the Total Physical Response (TPR) method of teaching vocabulary at British English School Makassar. The sample for the study included 28 junior students from British English School Makassar. A quantitative study design was employed to collect data relating to the perceptions of the pupils. The questionnaire functioned as the research instrument to help achieve the study’s objectives. The questionnaire was created using the questionnaire that Lin, Chan, and Hasio (2011) used to assess how EFL students felt about learning vocabulary in a computer-supported collaborative environment. A descriptive statistic was employed to analyze the data obtained from the surveys. There were two steps to the data analysis technique. First, the researcher assessed the students’ perceptions using a Likert scale. Second, converted the perception data from the students into a percentage analysis. Subsequently, the researcher employed the students’ statement category to interpret the students’ perspectives. The results verify that 23 or 82.14% of students gave very positive responses, and 5 or 17.86% of students gave positive responses. It revealed that using the Total Physical Response (TPR) method has helped pupils learn language more effectively because the positive environment in the classroom allowed students to enjoy the learning process.